PENGARUH UMUR PERUSAHAAN, AUDIT TENURE DAN GOOD CORPORATE GOVERNANCE PADA KECEPATAN PUBLIKASI LAPORAN KEUANGAN - Dewi, Kadek Indah Kusuma; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 15 No 1 (2016), 2016)
Velocity of ??publication from financial statement is important because it becomes the qualitative characteristics of useful information in support ing the relevance of the information. Besides how quickly a company publishes its financial statements will tend to affect the trust of financial statement users. The purpose of this study was to determine the effect of company age , the audit tenure and good corporate governance in velocity of ??publication from financial statements. The study was conducted on companies listed in the Indonesia Stock Exchange which is determined by the method of random sampling in the period 2011-2013. Samples were obtained by 26 companies , which are 60 observations and analyzed with multiple linear regression techniques. Based on the analysis found that the company age has no effect on the velocity of ??publication from financial statements. Audit tenure and good corporate governance has negativ e affect the velocity of ??publication from financial statements .
Keywords: company age, audit tenure, good corporate governance, velocity of publication from financial statements